Pelatihan Penanaman dan Teknologi Budidaya Durian (Durio zibethinus L.) di Desa Lebbek, Pamekasan, Madura - Marchel Putra Garfansa; Lia Kristiana; Yenni Arista Cipta Ekalaturrahmah; Endang Tri Wahyurini; Mohammad Taufiq Shidqi; Siti Holifah; Rahmawati Ardila; Mohammad Shoimus Sholeh; Fitrotin Nazizah (Institut Pertanian Bogor, 2025)
Lebbek Village is located in Pakong Sub-District, Pamekasan Regency, Madura, where the majority of the residents work as farmers. The village has an agricultural area of approximately 35,708 hectares. The cultivation of trees or perennial crops has become the preferred choice among the local community, as it not only creates a greener environment but also provides additional sources of income. One promising tree species for development in this area is durian. However, durian cultivation in Lebbek Village has generally been carried out without proper consideration of planting seasons, planting hole preparation, or sufficient knowledge of durian cultivation techniques. This program aimed to provide the local community with knowledge and understanding of best practices for planting and maintaining durian trees. The community engagement activities included educational sessions and hands-on training, followed by the distribution of questionnaires to assess the effectiveness of the outreach and training programs. Based on observations, the training activities were proven to deliver benefits and increase participants' knowledge. Questionnaire analysis showed a 55% improvement in participants' understanding compared to their initial knowledge before the training. Additionally, 67.5% of participants expressed agreement and satisfaction with the activities provided, with more than 15 individuals actively engaged in discussions and practical sessions on durian planting techniques. Collaboration with educational institutions and research organizations is recommended to provide advanced training and continuous innovation in durian cultivation as part of a sustainable development effort.